2008
DOI: 10.3238/arztebl.2008.0715
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy in Adults

Abstract: Only a comprehensive allergological evaluation performed by an experienced allergologist in accordance with current guidelines can protect patients from the negative consequences of excessive concern about a nonexistent food allergy (e.g., needless dietary restriction) or, on the other hand, the negative consequences of inadequate attention to a genuine food allergy (anaphylaxis). A proper evaluation consists of detailed allergologic history-taking, skin tests, and challenge tests when indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, DBPCFC is time-consuming, expensive, subjects patients to potential severe allergic reactions, requires the need for well equipped facilities and may not be able to reproduce the conditions that occurred when the reported allergic reaction took place [ 17 , 18 ]. Due to these practical problems, in normal clinical settings FA is often diagnosed by a thorough medical history and a test for sensitization [ 17 , 19 ]. In our study, medical history and sIgE was used to define a probable FA since this could be performed in all participants and outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…However, DBPCFC is time-consuming, expensive, subjects patients to potential severe allergic reactions, requires the need for well equipped facilities and may not be able to reproduce the conditions that occurred when the reported allergic reaction took place [ 17 , 18 ]. Due to these practical problems, in normal clinical settings FA is often diagnosed by a thorough medical history and a test for sensitization [ 17 , 19 ]. In our study, medical history and sIgE was used to define a probable FA since this could be performed in all participants and outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…With the clinical relevance of positive skin prick test and finding of food specific IgE limited by sensitization in patients, demonstration of a provoked allergy induced reaction in patient is the identified gold standard in diagnosis [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Reactions to an allergen may occur right away or at a later time (Gauerke, 2008; Seitz, Pfeuffer, Raith, Brocker, & Trautmann, 2008). For example, Seitz et al found that most symptoms occurred within 2 hours (69 percent) after ingestion of the allergen, whereas others occurred within 2 to 4 hours (28.6 percent).…”
Section: About Food Allergiesmentioning
confidence: 99%